STUDENTS' PERCEPTIONS OF THE USE OF DIGITAL MEDIA IN ENGLISH LANGUAGE LEARNING - Yolanda, Rizky (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study examines students' perceptions of the use of digital media in English language learning at Teacher Training and Education College of Insan Madani. Using a qualitative research approach, data were collected through semi-structured interviews with students enrolled in English language courses. The findings indicate that students perceive digital media as an effective and flexible tool that enhances their language acquisition. Platforms such as YouTube, Duolingo, Zoom, Google Classroom, and WhatsApp were particularly valued for their ability to provide authentic English exposure, interactive learning experiences, and opportunities for autonomous learning. However, despite the benefits, students also identified several challenges, including limited internet access, digital literacy gaps, and distractions from non-educational content. The study suggests that a blended learning approach, combining digital media with structured classroom instruction, could help mitigate these challenges and maximize the benefits of technology in English language learning. Additionally, institutions should focus on enhancing digital literacy training and improving internet accessibility to support students in effectively utilizing digital tools. This research contributes to the ongoing discourse on technology-enhanced language learning, particularly within the context of Islamic teacher training institutions, and provides insights for future studies on optimizing digital media use in English education.